224k views
1 vote
Solve the equation for the specified variable

S=gr-5gk*3, for g

User Alex Q
by
4.6k points

1 Answer

4 votes

Answer:


g = \sqrt{(S)/(3kr^(-5))}

Explanation:

Given


S=gr^(-5)gk*3

Required

Solve for g


S=gr^(-5)gk*3

Split into different entities


S=g * r^(-5)*g*k*3

Reorder in terms of like terms


S=g*g * r^(-5)*k*3


S=g^2 * r^(-5)*k*3


S=g^2 * 3kr^(-5)

Solve for
g^2


g^2 = (S)/(3kr^(-5))

Take square root of both sides


g = \sqrt{(S)/(3kr^(-5))}

User Ankit Ladhania
by
5.3k points